2019
DOI: 10.1037/str0000108
|View full text |Cite
|
Sign up to set email alerts
|

Major life events in family life, work engagement, and performance: A test of the work-home resources model.

Abstract: This weekly diary study (N ϭ 185 persons, n ϭ 443 occasions) investigates how major life events influence weekly resource use, work engagement, and job performance. On the basis of the work-home resources model, we propose that weekly rumination undermines effective use of personal resources (i.e., self-efficacy), whereas weekly psychological detachment from the major life events facilitates effective use. In addition, we hypothesize that work role centrality acts as a key resource, and amplifies the two-way i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 51 publications
5
57
1
1
Order By: Relevance
“…Theoretical Implications. These longitudinal results are in line with those from prior studies showing that work engagement is more strongly related to individual differences than to environmental factors (Bakker, Du, & Derks, 2018;Kim & Beehr, 2018). For instance, Salmela-Aro and Upadyaya (2018) showed that the effects of personal resources (resilience) on work engagement were stronger than those of job resources (ability to work, team climate, and role in the organization) in the mid-and late career stages.…”
Section: A Longitudinal Perspectivesupporting
confidence: 89%
“…Theoretical Implications. These longitudinal results are in line with those from prior studies showing that work engagement is more strongly related to individual differences than to environmental factors (Bakker, Du, & Derks, 2018;Kim & Beehr, 2018). For instance, Salmela-Aro and Upadyaya (2018) showed that the effects of personal resources (resilience) on work engagement were stronger than those of job resources (ability to work, team climate, and role in the organization) in the mid-and late career stages.…”
Section: A Longitudinal Perspectivesupporting
confidence: 89%
“…In this line of reasoning, the Covid-19 pandemic is a normative history-graded life event influencing older adults’ development. Such a life event can be disruptive ( Akkermans, Seibert, & Mol, 2018 ) and can lead to the depletion of one’s personal resources ( Ten Brummelhuis and Bakker, 2012 ) and to person-environment misfit ( Kooij, Zacher, Wang, & Heckhausen, 2020 ), thus harming work outcomes ( Bakker, Du, & Derks 2018 ). Similarly, Akkermans, Richardson, and Kraimer (2020) suggest that Covid-19 is a career shock, which might disrupt career outcomes by causing resource loss cycles.…”
Section: A Lifespan Development Perspective: Engaging In Self-regulatmentioning
confidence: 99%
“…The daily processes of work-family conflict and enrichment have been analyzed in various studies (Bakker et al, 2019;Brosch & Binnewies, 2018;Du et al, 2018;Haar et al, 2018;Ilies et al, 2009). However, only two of these studies (Brosch & Binnewies, 2018;Du et al, 2018) refer to the Work-Family Resource Model.…”
Section: The Daily Processes Of Work-to-family Conflict and Enrichmentmentioning
confidence: 99%